Growth, physiological, and molecular responses of broiler quail to dietary source, particle size, and choice feeding of calcium - Reza Bagheri; Majid Toghyani; Sayed Nouredin Tabatabaei; Sayed Ali Tabeidian; Maryam Ostadsharif (Italian Journal of Animal Science, 2022)
Two experiments were performed to explore the effect of dietary supplemental different sources and particle sizes of calcium (Ca) on growth performance, bone mineralisation, blood attributes, and calbindin gene expression in broiler quail. In experiment 1, 480-day old broiler Japanese quail (Coturnix japonica) were allotted to four dietary treatments based on a factorial arrangement (2 × 2) consisting of basal diets formulated either with limestone or oyster shell with coarse or fine particles. Supplemental coarse oyster shell impaired growth performance and Ca intake compared to coarse limestone (p < .05). The concentration of blood Ca was lower in birds who received supplemental coarse or fine oyster shell than coarse limestone (p < .05). Higher expression of calbindin gene observed in birds fed on the coarse oyster shell (p < .05). In experiment 2, a total of 360 Japanese quail assigned to experimental treatments of feeding: (1) control: a basal diet; (2) choice feeding between a Ca deficient diet and limestone with coarse (granulated) and fine particles; (3) choice feeding between a Ca deficient diet and oyster shell with coarse and fine particles. All birds preferred to use fine Ca particles across the first week of the experiment (p < .05) whereas tended to consume higher fine oyster shell during the entire rearing period (p < .05). Feed conversion ratio impaired in birds subjected to choice feeding (p < .05). Overall, coarse oyster shell decreased the growth of birds in the first experiment. The overall growth of choice-fed birds depressed compared to when received one conventional feed.HIGHLIGHTS Growth of quail decreased when they fed on diets containing coarse oyster shell. Higher expression of calbindin gene observed in quail received coarse oyster shell. Quail tended to use a separate source of Ca when fed with a Ca deficient diet.